Pelatihan Merawat Jenazah Laki-Laki (Mengkafani) - Muhamad Khoirur Roziqin; Ospa Pea Yuanita Meishanti; Muhammad Shohibul Mafariech (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2022)
The students at the As Saidiyyah 1 Bahrul Ulum Islamic Boarding School in Jombang experienced many obstacles / obstacles in implementing training on caring for corpses. The obstacle that occurs in the care of the corpse at Pondok Pesantren As-Saidiyyah 1 Bahrul Ulum Tambakberas Jombang, this is the lack of adequate teaching aids / manuals for caring for the corpse. So that the interest in learning from students is not so great, even though the law of caring for corpses is mandatory. The approach method for the implementation of this santri service activities includes lectures, discussions, and workshops (training). It is concluded that training in caring for the corpse is very much needed by the students.